THE IMPLEMENTATION OF THE JOINT AGREEMENT IN THE FORM OF COMPENSATION FOR TERMINATION OF EMPLOYMENT THAT CONTRARY TO LABOR LAW - Yusuf Randi (JURNAL HUKUM DE'RECHTSSTAAT, 2020)
Humans as social creatures always work, either endeavored alone or work with others in meeting their needs, which then gave birth to work relationships. The working relationship in the journey does not always run harmoniously but there are often disputes that sometimes end with the termination of employment (PHK), as happened in the Supreme Court Decree No: 788k/Pdt.Sus-PHI/2018, where the company laid off workers against and provide compensation for layoffs based on collective agreements and are not guided by the provisions of layoffs in Law No. 13 concerning Manpower.The method of approach used is normative juridical, with research specifications analytical descriptive. The results showed that the joint agreement applied by the Supreme Court Judge as a legal basis in resolving cases, defects an objective requirement that is violating the halal causal conditions, because it regulates layoff compensation whose value is not under the provisions of Article 156 paragraph (1), (2), (3) and (4) the Manpower Act, thus violating the legal conditions of the agreement in Article 1320 of the Civil Code, therefore the agreement is invalid and has no legal force. Besides, the work period of workers with companies based on PKWT should legally change to PKWTT as stipulated in Article 59 paragraph (7) of the Manpower Act.Keywords: Compensation,  Work termination, Joint Agreements.